ANALISA KANDUNGAN GIZI DAN DAYA TERIMA CRACKERS DENGAN PEMANFAATAN TEPUNG DAUN KELOR DAN TEPUNG IKAN LELE - lily meilani sidabutar; Evawany Y Aritonang; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
The problem of Protein Energi Malnutrition in children under five is a very difficult problem to overcome, the cause of malnutrition is basically a simple deficiency in food consumption. Tackling Protein Energi Malnutrition can be done by increasing protein intake. Withgiving of food, like crackers. But most crackers have carbohydrates while the protein content is relatively low. So make crackers by utilizing moringaleaves flourand catfish flour to improve the nutritional composition. Type of research was experiment. The study used a complete randomized design with a organoleptic test to see the panelist's preference level on the test food. Organoleptic test subjects amounted to 30 people students of FKM USU. The object of this study were crackers with moringaleaves flourand catfish flour treatment A1 (15gr and 50gr), A2 (20gr and 45gr) and A3 (25gr and 40gr) from the weight of the main ingredient. The nutrition content seen include fat, protein, iron, and calcium. Crackers with moringaleaves flourand catfish flour have the highest protein content of 16.0% found crackers with 25gr moringaleaves flour and 40gr catfish flour. The highest fats were found in crackers with 15gr moringaleaves flourand 50gr catfish flour which was 22.3%. The highest iron are crackers with 25gr moringaleaves flourand 40gr catfish flour which is big 10.4% while the highest calcium is 5.42% found in crackers with 25gr moringaleaves flourand 40gr catfish flour. The results of the organoleptic test, the panelists most liked crackers with moringaleaves flour15gr and 50gr catfish flour in color, aroma and taste indicator which each have a score of 88.8%, 79.9%, 85.5% with likes criteria, whereas for panelist textures most liked crackers with 25gr moringaleaves flourand 40gr catfish flour which has a score of 78.8% with the likes criteria. Crackers produced can be used as additional food. Moringa leaves and catfish can be recommended for ingredients in the manufacture of crackers that have protein content. Keywords: Crackers, Organoleptic Test, Moringa leaves, Catfish, Nutrient Content